2016
DOI: 10.14309/crj.2015.91
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Paraesophageal Hematoma

Abstract: Spontaneous paraesophageal hematoma (SPH) likely shares a common etiology with spontaneous intramural esophageal hematoma (IEH). Patients with IEH typically present with hematemesis or melena leading to early detection and management, but patients with SPH do not have overt gastrointestinal bleeding on presentation. Management depends on the correction of the underlying causative factor. We present the first case of a spontaneous paraesophageal hematoma in a patient with hemophilia B. Awareness of this complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Patients are kept nil by mouth initially and maintained on IV fluids and NG/NJ feeding, with gradual reintroduction of a soft diet. In the majority case studies reported to date, patient outcomes have been good with complete resolution of lesions and no long-term complications [ 9 ]. In extremely rare cases, angiography and embolization or surgical intervention is mentioned, probably when a distinctive oesophageal pathology is eventually identified [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients are kept nil by mouth initially and maintained on IV fluids and NG/NJ feeding, with gradual reintroduction of a soft diet. In the majority case studies reported to date, patient outcomes have been good with complete resolution of lesions and no long-term complications [ 9 ]. In extremely rare cases, angiography and embolization or surgical intervention is mentioned, probably when a distinctive oesophageal pathology is eventually identified [ 10 ].…”
Section: Discussionmentioning
confidence: 99%